Home/land/security [ what we learn about Arab communities from action-adventure films - Wilkins, Karin Gwinn , 1962- (Lexington Books, 2009)
"Karin Gwinn Wilkins interviews focus groups composed of a diverse cross-section of Americans and analyzes their interpretations of action-adventure film villains of Middle Eastern descent. Wilkins addresses the neglected empirical link between documented media stereotypes of Arab communities and the lived consequences of these portrayals, both in terms of discriminatory practices and generalizations."--BOOK JACKET.